If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=-6(6+x)
We move all terms to the left:
-6-(-6(6+x))=0
We add all the numbers together, and all the variables
-(-6(x+6))-6=0
We calculate terms in parentheses: -(-6(x+6)), so:We get rid of parentheses
-6(x+6)
We multiply parentheses
-6x-36
Back to the equation:
-(-6x-36)
6x+36-6=0
We add all the numbers together, and all the variables
6x+30=0
We move all terms containing x to the left, all other terms to the right
6x=-30
x=-30/6
x=-5
| 7x+4=3×+5 | | 2+5z=62 | | b/2+5=8 | | 7x-10=26+x | | 165-w=228 | | 3n=7n-6 | | m/3+17=19 | | 15=z3+11 | | 4(26+x)=2(17+2x) | | 3a=12-2 | | 48=8(w-5) | | 200+0.25x=382.50 | | 4(2+x)=2(17+2x) | | 4(2+x)=4(17+2x) | | 12m-3=18-9m | | 3s-14=-23 | | 4(2+x)=4(7+2x)+5 | | 12+4u=0 | | 2w-4=0 | | 4(2+x)=2(7+2x) | | 12-4w=0 | | 4(2+x)=4(7+2x) | | 7+-s=10 | | 5x+3(-2x+4)=10 | | 0.06(7-9)+0.12y=0.20y-0.7 | | 5X+4y=17.4 | | -8(-2a+4)-1=-145 | | 4x-2(x-4)=9+4x+11 | | 4w+28=12 | | 8x^2-7x+2=0 | | 2(-y-1)+5y=7 | | 5(7+n)=-35 |